2016
DOI: 10.1177/107327481602300406
|View full text |Cite
|
Sign up to set email alerts
|

Black Heterogeneity in Cancer Mortality: US-Blacks, Haitians, and Jamaicans

Abstract: Introduction The quantitative intraracial burden of cancer incidence, survival and mortality within black populations in the US is virtually unknown. Methods We computed cancer mortality rates of US- and Caribbean-born residents of Florida, specifically focusing on black populations (US, Haiti, Jamaica) and compared them using age-adjusted mortality ratios obtained from Poisson regression models. We compared the mortality of Haitians and Jamaicans residing in Florida to populations in their countries of orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 65 publications
(58 reference statements)
9
59
0
2
Order By: Relevance
“…Thus, in our study, lower incidence and better survival in the US, due to widely available screening, potential for early detection, and access to treatment including radiotherapy for middle and late stages, likely explains the markedly lower mortality rates among populations of Mexican origin living in the US compared to Mexico . Similar patterns of substantially lower mortality rates from cervical cancer among immigrants compared to the country of origin were reported for non‐Hispanic immigrants from Haiti and Jamaica, demonstrating the efficacy of cervical cancer control programs in the US for foreign‐born minority women. While it is possible that oncogenic HPV prevalence rates differ between Mexico and the US, the lack of difference in mortality between Mexican Immigrants and Mexican Americans in California suggests that cervical cancer screening and access to healthcare might be more important determinants of the considerably lower mortality in the US than variations in HPV risk.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, in our study, lower incidence and better survival in the US, due to widely available screening, potential for early detection, and access to treatment including radiotherapy for middle and late stages, likely explains the markedly lower mortality rates among populations of Mexican origin living in the US compared to Mexico . Similar patterns of substantially lower mortality rates from cervical cancer among immigrants compared to the country of origin were reported for non‐Hispanic immigrants from Haiti and Jamaica, demonstrating the efficacy of cervical cancer control programs in the US for foreign‐born minority women. While it is possible that oncogenic HPV prevalence rates differ between Mexico and the US, the lack of difference in mortality between Mexican Immigrants and Mexican Americans in California suggests that cervical cancer screening and access to healthcare might be more important determinants of the considerably lower mortality in the US than variations in HPV risk.…”
Section: Discussionsupporting
confidence: 74%
“…Creque et al reported similar survival findings in a cohort of multinational urban black women with uterine cancer, although they included uterine sarcomas in the analyses 12. Pinheiro et al used statewide cancer registry data to evaluate mortality among women with endometrial cancer and found that Jamaicans had higher mortality than US born blacks, but that mortality among Haitians and other West Indian women was lower 11. However, patients were not stratified by histologic grade in their analyses.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, of all Hispanic groups, Dominicans had the highest proportion of black race in our dataset. Men of African ancestry are known to have high prostate cancer incidence and mortality rates (16, 23), particularly for aggressive forms that present in late stages (24). Dominicans, with the highest prostate cancer mortality among Hispanic groups in Florida, also have the lowest documented rates of prostate cancer screening (25).…”
Section: Discussionmentioning
confidence: 99%